2011
DOI: 10.1080/07399332.2011.603858
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and Daughters: Intertwining Relationships and the Lived Experience of Breast Cancer

Abstract: No relationship is more profound than the positional mother- daughter dyad. Each shares a physical, emotional, and spiritual link not experienced by others. The intrusion of breast cancer alters this normative dyadic relationship. In this article we explore this change through a hermeneutic reflective narrative inquiry, incorporating Bakhtinian dialogism, of the behavioral science literature, popular press, and other resources, and use of the motet to uncover the lived experience of women in this dyadic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…As indicated in the literature, the mother‐daughter relationship is complex, and although it can be positive, it also is subject to strain . The added pressure of a breast cancer diagnosis and issues surrounding weight control can further stress the relationship, making participation in a mother‐daughter weight loss intervention perhaps less productive than if survivors of cancer were provided free choice in selecting a teammate for the partner‐based intervention, as in the aforementioned study by Gorin et al Through implementation of the current study, we found that focusing recruitment solely on mother‐daughter dyads served as a considerable barrier because many survivors of breast cancer did not have biological daughters or did not want to participate in a weight loss intervention with them. Likewise, similar barriers were observed among daughters.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…As indicated in the literature, the mother‐daughter relationship is complex, and although it can be positive, it also is subject to strain . The added pressure of a breast cancer diagnosis and issues surrounding weight control can further stress the relationship, making participation in a mother‐daughter weight loss intervention perhaps less productive than if survivors of cancer were provided free choice in selecting a teammate for the partner‐based intervention, as in the aforementioned study by Gorin et al Through implementation of the current study, we found that focusing recruitment solely on mother‐daughter dyads served as a considerable barrier because many survivors of breast cancer did not have biological daughters or did not want to participate in a weight loss intervention with them. Likewise, similar barriers were observed among daughters.…”
Section: Discussionmentioning
confidence: 79%
“…In defining the term “cancer survivor,” the National Coalition for Cancer Survivorship includes family, friends, and caregivers, because the impact of cancer is far‐reaching. Observational studies have suggested that the mother‐daughter relationship may be particularly affected by a cancer diagnosis, especially breast cancer . Sinicrope et al have suggested that the mother‐daughter relationship can be leveraged specifically to deliver messages regarding cancer prevention and control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other articles addressed coping and communication strategies among cancer patients and carers (Donovan‐Kicken et al . , Olson ), trust‐building (Katzman ), and positive relationships in families (see Wiggs on mother daugher relationships). Towsley et al .…”
Section: Living With and Beyond Cancermentioning
confidence: 99%